2017
DOI: 10.1111/cas.13394
|View full text |Cite
|
Sign up to set email alerts
|

Elevated expression of ΔNp63 in advanced esophageal squamous cell carcinoma

Abstract: This study aims to explore the expression level of ΔNp63 in esophageal squamous cell carcinoma (ESCC). To investigate the association between ΔNp63 (p40) expression and ESCC biology, we compared the levels of ΔNp63 expression in normal and tumor tissues, with a specific focus on the diagnostic value of ΔNp63 in ESCC. We analyzed 160 consecutive patients with ESCC who underwent surgical resection without neoadjuvant chemotherapy at Gunma University Hospital (Maebashi, Japan) between September 2000 and January 2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
15
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 14 publications
(16 citation statements)
references
References 38 publications
1
15
0
Order By: Relevance
“…7H). In line with our previous report using lung SCC specimens (24), higher levels of Stxbp4 expression were significantly correlated with the accumulation of ΔNp63 (23,34) and with prognosis according to the combined lung SCC dataset from The Cancer Gene Atlas (SI Appendix, Fig. S9) (35).…”
Section: δNp63α Protein Is Regulated By the Apc/c During The Cell Cycsupporting
confidence: 88%
See 1 more Smart Citation
“…7H). In line with our previous report using lung SCC specimens (24), higher levels of Stxbp4 expression were significantly correlated with the accumulation of ΔNp63 (23,34) and with prognosis according to the combined lung SCC dataset from The Cancer Gene Atlas (SI Appendix, Fig. S9) (35).…”
Section: δNp63α Protein Is Regulated By the Apc/c During The Cell Cycsupporting
confidence: 88%
“…Purification of the doubly tagged ΔNp63α complex and MALDI-TOF mass analysis and immunohistochemical analysis were as previously described (48,49). Immunohistochemistry and scoring methods were as previously described (24,34). Details of extended methods used in this paper including cell culture, antisense oligonucleotides, baculovirus protein purification, cell synchronization, FACS analysis, far-Western immunoblotting, in vitro ubiquitination assay, in vitro degradation assay, immunofluorescence, immunohistochemistry, real-time qPCR, 3D organotypic raft cultures, anchorage-independent growth assay, and s.c. transplantation in mice are described in SI Appendix, SI Materials and Methods.…”
Section: Methodsmentioning
confidence: 99%
“…DeltaNp63 was reported to play a crucial role in keratinocyte differentiation and its expression was shown to be a defining feature of basal cells and squamous cell carcinomas (12)(13)(14). Concordantly, deltaNp63 is expressed in many squamous-like cancers, including esophageal squamous cell carcinoma (15,16), head and neck squamous carcinoma (17), and lung squamous cell carcinoma (18,19). p63 was found to drive epidermal differentiation through distal regulatory elements associated with its target genes (20).…”
mentioning
confidence: 98%
“…ΔNp63 in breast and esophageal squamous carcinoma was previously reported to act as an activator of cell migration and invasion [ 30 , 31 ]. ΔNp63 was also highly expressed in several cancer tissues such as esophageal squamous cell carcinoma and cervical cancer with poor prognosis [ 22 , 32 ]. Similarly, our results also demonstrated that ΔNp63 induces apoptosis and activates migration and invasion in cervical cancer cells.…”
Section: Discussionmentioning
confidence: 99%